Actinomycetes as host cells for production of recombinant proteins - Tamura Tomohiro; Mitani Yasuo; Nakashima Nobutaka (Microbial Cell Factories, 2005)
Abstract Actinomycetes (Actinobacteria) are highly attractive as cell factories or bioreactors for applications in industrial, agricultural, environmental, and pharmaceutical fields. Genome sequencing of several species of actinomycetes has paved the way for biochemical and structural analysis of important proteins and the production of such proteins as recombinants on a commercial scale. In this regard, there is a need for improved expression vectors that will be applicable to actinomycetes. Recent advancements in gene expression systems, knowledge regarding the intracellular environment, and identification and characterization of plasmids has made it possible to develop practicable recombinant expression systems in actinomycetes as described in this review.